Uncommon ground : The music of Michael Finnissy - Brougham, Henrietta; Fox, Christopher; Pace, Ian (Hants Ashgate, 1997)
This book looks at the life and works of Michael Finnissy, and focuses on his piano music, chamber music, orchestral music, vocal music and his theatrical works. It also includes a catalogue of his work.